2014
DOI: 10.3748/wjg.v20.i7.1712
|View full text |Cite
|
Sign up to set email alerts
|

Clinical approaches to non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) ranges from simple steatosis to nonalcoholic steatohepatitis (NASH), leading to fibrosis and potentially cirrhosis, and it is one of the most common causes of liver disease worldwide. NAFLD is associated with other medical conditions such as metabolic syndrome, obesity, cardiovascular disease and diabetes. NASH can only be diagnosed through liver biopsy, but noninvasive techniques have been developed to identify patients who are most likely to have NASH or fibrosis, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
100
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 111 publications
0
100
2
1
Order By: Relevance
“…It is important to highlight that patients with normal transaminases and hepatic steatosis (ultrasound) may also have NASH and liver fibrosis (18,19). Recent studies reported that there is no optimal level of ALT to predict NASH and advanced fibrosis (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that patients with normal transaminases and hepatic steatosis (ultrasound) may also have NASH and liver fibrosis (18,19). Recent studies reported that there is no optimal level of ALT to predict NASH and advanced fibrosis (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…If NAFLD is neither identified in its early stages nor managed appropriately, the disease will naturally progress to the severe NASH stage, which entails inflammation, fibrosis, and cirrhosis [3]. Non-invasive US imaging is an appropriate first-line method for the early detection of asymptomatic NAFLD [40].…”
Section: Weta Et Almentioning
confidence: 99%
“…Non-invasive US imaging is an appropriate first-line method for the early detection of asymptomatic NAFLD [40]. Schwenger et al [3] recommended that an improvement in diet and increase in physical activity should be the first choice to treat NAFLD, followed by the management of insulin resistance, oxidative stress, and obesity-associated morbidity.…”
Section: Weta Et Almentioning
confidence: 99%
See 2 more Smart Citations